Colmar - Unterlinden Museum - In Alsace. News from France 1874 by... - Txllxt TxllxT (Wikimedia Commons, 2023)
Notice iconographique issue de Wikimedia Commons. Titre: Colmar - Unterlinden Museum - In Alsace. News from France 1874 by Gustave Brion (1824-1877) - Oil on Canvas. Colmar - Unterlinden Museum - In Alsace. News from France 1874 by Gustave Brion (1824-1877) - Oil on Canvas
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons